Fingerprinting of monovarietal olive oils from Argentina and Uruguay via stable isotope, fatty acid profile, and chemometric analyses - Spangenberg, Jorge Enrique (2024)
Fil: Spangenberg, Jorge Enrique. University of Lausanne. Institute of Earth Surface Dynamics (IDYST); Suiza